2011
DOI: 10.1177/0306624x11402945
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense, Making Good, or Making Meaning? Cognitive Distortions as Targets of Change in Offender Treatment

Abstract: Most structured sex-offender programs are based on a cognitive-behavioural model of behaviour change. Within this overarching theoretical paradigm, extensive use of cognitive distortions is seen as a central core symptom among sex offenders. However, the literature on cognitive distortions lacks a clear and consistent definition of the term. It is unclear whether cognitive distortions are consciously employed excuses or unconscious processes serving to protect the offender from feelings of guilt or shame. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…Waldram () previously suggested that cognitive distortions may serve the purpose of supporting the offender's morale via a narrative approach. A similar suggestion was made by Friestad (), who suggested that cognitive distortions could be indicative of an attributional bias.…”
Section: Treatment Studiessupporting
confidence: 74%
See 1 more Smart Citation
“…Waldram () previously suggested that cognitive distortions may serve the purpose of supporting the offender's morale via a narrative approach. A similar suggestion was made by Friestad (), who suggested that cognitive distortions could be indicative of an attributional bias.…”
Section: Treatment Studiessupporting
confidence: 74%
“…Furthermore, a recent meta-analysis found that programs that utilize arousal reconditioning had larger treatment effects (Gannon et al, 2019). As cognitive distortions can start and maintain sexual offense patterns (Hazama & Katsuta, 2019;O'Ciardha & Ward, 2013), CBT is often included in sex offender treatment programs to address cognitive distortions (Friestad, 2012). In Western cultures, the most common cognitive distortions were denial or minimization of guilt, problematic sexual interests, harm to victims, responsibility for the offenses, and need for treatment (Nunes & Jung, 2013).…”
Section: Aroudj and Barattamentioning
confidence: 99%
“…, p.6) is identified as a common feature of the initial process of desistance. Therefore, reflecting on one's own life history – reassessing where one is now and where one wants to be – involves this subjective narrative, a conversation with, and examination of, the self that carries ‘the potential of influencing future action’ (Friestad , p.473). In short, it is hard for anyone unpractised in these subjective skills, to think about one's own feelings or imagine the feelings of others (Adshead ), or reflect on the impact of these feelings and actions on others (McKendy ; Pryor ).…”
Section: Subjective Changes and Identity Transformationmentioning
confidence: 99%
“…Emotional learning increases knowledge about oneself and the ‘act of analysis inevitably alters the experience and the learning that flows from it’ (Rose, Loewenthal and Greenwood , p.444). Therefore, narrative takes on importance as the ‘vehicle through which selfhood is created and recreated’ (Friestad , p.475). As one offender who had attended the reading group‐based activity put it:
I have gained more insight and knowledge here than anywhere else.
…”
Section: Evidence Of Emotional Learningmentioning
confidence: 99%
“…Cognitive distortions are beliefs that support sexual offending including justifications and excuses (Nunes & Jung, 2012) that can occur unconsciously or consciously (Friestad, 2012;Wright & Schneider, 1999). Often, definitions of cognitive distortions include denial and minimization, however they appear to be distinct concepts.…”
Section: Deviant Sexual Interestsmentioning
confidence: 99%